Cuidado ético e convivência nos anos iniciais do ensino fundamental - Kokott, Vanessa (2017)
This dissertation presents a qualitative, exploratory and analytical investigation, focusing on the construction of the coexistence among students in the initial years in Elementary School from the perspective of ethical care practices. In the first part of the research, we present a chapter that explores contemporary education and the ethics of care, and another that deals with school coexistence. The theoretical framework was developed by authors such as, Morin (2003, 2007, 2007a, 2011, 2016), Baptista (2005), UNESCO (2016), Delors (2010), Gómez (2007), Fierro Evans (2013), Fierro Evans and Mena (2008), Fierro Evans and Carbajal (2003), Fierro Evans et al. (2013), Fierro Evans and Tapia (2013), Mena and Romagnoli (1993), Mena and Ramírez (2003), Garcia (2016), Noddings (1988, 1996, 1999, 2002a, 2002b, 2003, 2005, 2006, 2010, 2010a), Boff (2012, 2013, 2014), Verdera (2009, 2010, 2012), among others. In the second section, we present the research methodology, which presents the field work, which aims to identify the educational practices of ethical care exercised by a group of teachers and coordinators to build the coexistence between students in the early years of Elementary School . For data collection in the field, semi-structured interviews were applied, following guidelines found in Triviños (1987) and Minayo (2013), with 7 teachers and 2 coordinators who work in the initial years of Elementary Education, and who have significant experiences related to coexistence And ethical care among students at that level of education. The selection followed criteria of intentional sampling by intensity, based on Patton (1990). Regarding the interpretation of the collected data, the Content Analysis method, proposed by Bardin (1988), was used. As a result of the analysis of the content of the interviews, we developed the following categories: moral coexistence, affective coexistence, personifying a moral reference, guiding coexistence through true dialogue, solidarity action in school, loving presence and continuous daily closeness. Based on the analysis and interpretation of the categories, we identified the ethical care practices practiced by the teachers and coordinators in that school, which encompass true dialogue, the activities in which the students provide solidary help, and the continuous daily closeness between all Involved in the educational process. These aspects are fundamental to the construction of coexistence between students in the initial years of Elementary School.